2021
DOI: 10.1007/s13187-020-01950-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient Satisfaction Among Cancer Patients Undergoing Radiotherapy

Abstract: The patient-provider relationship is a key driver of patient satisfaction as it relates to overall healthcare experience. We surveyed patients undergoing radiation therapy to determine what they consider to be the most valued qualities in their interactions with the healthcare team. An ethics-approved 35-item patient satisfaction survey was developed in-house to gain insights on patients’ perception of their relationship with the healthcare team throughout their cancer journey. There were 199 completed survey,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…According to the participants' experiences, the category of behavioral abnormalities in the relationship between patients and nurses consisted of the subcategories of patients' unjustified expectations and increased expectations. In agreement with these observations, Samant et al revealed that patients hospitalized in oncology wards due to their special mental conditions are more sensitive to non-verbal communications with nurses and have higher expectations than other patients (16). In this regard, the participating nurses emphasized the abnormalities in the relationship due to the patient's factors and characteristics, including the close relationship between the patient and the nurse, and expressed it in various ways.…”
Section: Discussionmentioning
confidence: 83%
“…According to the participants' experiences, the category of behavioral abnormalities in the relationship between patients and nurses consisted of the subcategories of patients' unjustified expectations and increased expectations. In agreement with these observations, Samant et al revealed that patients hospitalized in oncology wards due to their special mental conditions are more sensitive to non-verbal communications with nurses and have higher expectations than other patients (16). In this regard, the participating nurses emphasized the abnormalities in the relationship due to the patient's factors and characteristics, including the close relationship between the patient and the nurse, and expressed it in various ways.…”
Section: Discussionmentioning
confidence: 83%
“…They revealed that advanced evidence-based practice nursing improved patient satisfaction. Furthermore, Samant et al(2021) and Lichen et al (2021), who assessed the relationship between nursing care and patient satisfaction, showed a strong relationship between the nursing care delivered and patient satisfaction. Additionally, Karaca and Durna (2019) concluded that patients were more satisfied with nurses' attention and care.…”
Section: Discussionmentioning
confidence: 99%
“…Part II: Patient satisfaction with NCBs evaluation scale This part was developed by the researchers after reviewing the related literature (Akgün et al, 2020;Lucadamo et al, 2021;Molalign Takele et al, 2021;Samant et al, 2021). This part was used to evaluate the participated patient satisfaction with the nursing interventions based on NCBs protocol.…”
Section: Tool For Data Collectionmentioning
confidence: 99%
“…Patients’ satisfaction assessment is recognized as an important tool for evaluating the needs of patients and identifying the areas for improvement in a healthcare organization [ 14 ]. This perception may vary according to socioeconomic aspects, healthcare system resources and related patient expectations [ 17 ]and can be carried out using different tools even in low-income countries with limited technological models such as the EORTC (EORTC IN-PATSAT32) care questionnaire to measure patients appraisal, care organization and services [ 12 ]. Moreover, cancer patients’ concerns regarding the long waiting times for radiation treatment and LINAC disruptions could have negative impacts on quality of care and on patient perceptions of treatment effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, activating a customer satisfaction tool for patients in a radiation oncology department can allow for evaluating the quality of daily work performed and how to improve its processes [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%